Factors predicting early re-bleeding and in-hospital mortality after acute variceal hemorrhage in patients with cirrhosis - Shrestha, Roshan; Karki, Sanjit; Sharma, Yuba Raj (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Risk factors for early re-bleeding and in-hospital mortality following acute variceal hemorrhage (AVH) are incompletely understood. The aim of this study was to find out the risk factors for early re-bleeding within 5 days and in-hospital mortality after AVH in patients with cirrhosis.Method: This was an analytical cross-sectional study conducted in Department of Medicine, Patan Hospital, Patan Academy of Health Sciences (PAHS), Nepal from July 2021 to June 2022. The ethical clearance was obtained from the Institutional Review Committee-PAHS. Informed consent was taken from the patients. Patients aged >18 y with diagnosed case of liver cirrhosis and endoscopy confirmed variceal bleeding were enrolled. All cases of early re-bleeding within 5 days and in-hospital outcome were recorded.Result: In this study total 72 patients were enrolled. The mean age of our patients was 51.68 y. Sixty seven (93%) of the patients improved, 3(4.16%) had early re-bleeding and 5(6.9%) died during the same hospital admission. Univariate analysis showed that early re-bleeding was significantly associated with the high PT/INR (p